Determination of in vitro antidiabetic of clinacanthusnutans extracts - Nuraini Abdullah (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Diabetes mellitus is a prevalent disease which characterized by hyperglycemia. It is a condition in which blood glucose levels are elevated due to decrease in cellular glucose uptake and metabolism. The management of blood glucose level is critical in the treatment of this disease and this had been offered by alpha amylase inhibitors. The present study was designed to determine the in vitro antidiabetic of Clinacanthus nutans extracts. The antidiabetic action was observed by the inhibition effects of the C. nutans extracts on alpha amylase activity and glucose diffusion across the dialysis tube. It was found that the antidiabetic action of the C. nutans extracts was not related to glucose diffusion since they did not show any significant glucose entrapment ability. The ethanolic leaves extract of C. nutans exhibited the most significant inhibition effect on alpha amylase activity (64.25%) as compared to other extracts. However, its inhibitory activity was moderate when compared to the commercial drugs as control (captopril & acarbose). The ethanolic leaves extract (the best extract) was tested for the presence for flavonoids, saponins and tannin (most reported antidiabetic compounds). Its antidiabetic action might be due to the presence of flavonoids and tannins. However, the absence of saponins might be responsible for its moderate inhibition effect comparable to control. This study suggested the in vivo studies on this plant to confirm its antidiabetic mechanism